Are we bullies? Creating a culture of respect. Reducing or eliminating bullying in workplaces - Erna Sovic Þórarinsdóttir 1976- (2016)
The purpose of this thesis for an MS degree in Human Resource Management is to ascertain the level of workplace bullying and how it affects employee sick leave and employees’ wishes to quit their jobs, at a company in Iceland. The research question is: Does bullying take place in the organization? Two hypotheses were proposed. The first one is that exposure to bullying is positively linked to intention to leave the company and the second one is that exposure to bullying is positively linked to more frequent sick leave. There are four main chapters in the thesis. The first one is a literature review, where key concepts and definitions are presented. Next is a chapter about the effects of workplace bullying, on those who experience it as well as the organization where it takes place. This is followed by a chapter covering the methodological part of the research, where important findings are discussed. A questionnaire was sent to 351 employees at a company in the private sector in the capital area of Iceland. Complete data was received from 193 individuals, which gives a response rate of 54,99%. The fourth chapter covers organizational measures which can be taken to prevent or reduce workplace bullying. The main findings suggest that employees who are exposed to bullying in the workplace, are more likely to want to quit their job in the next six months and are more frequently absent from work due to sickness than employees who are not exposed to workplace bullying. The research also shows how important it is that managers are provided with appropriate training in order to promote respectful behavior among their subordinates and to successfully deal with incidents of workplace bullying, and that this is one of the key components of a respectful working culture in organizations. Markmið þessa rannsóknarverkefnis til meistaraprófs í mannauðsstjórnun er að rannsaka hversu algengt einelti er í fyrirtæki á höfuðborgarsvæðinu, ásamt því hvaða áhrif það hefur á veikindaleyfi starfsfólks og hversu líklegt starfsfólk er ...